Legal Analysis of the Element of Premeditation in Article 340 of the Criminal Code Regarding Premeditated Murder (Case Study Of Decision Number: 907/PID.B/2020/PN MDN) - Widya Anisah; Khomaini Khomaini; Ramadhany Nasution (Fox Justi : Jurnal Ilmu Hukum, 2026)
This study aims to analyze the elements of criminal acts in Article 340 of the Criminal Code (KUHP) concerning premeditated murder proven in the primary indictment against the defendant Zuraida Hanum in the Medan District Court Decision Number: 907/Pid.B/2020/PN Mdn. In addition, this study also aims to determine the motives and factors that caused the defendant to commit premeditated murder. This study uses a normative juridical approach with a descriptive-analytical method, namely by examining secondary data in the form of legislation, legal literature, and related court decisions. Based on the results of the study, it was found that all elements in Article 340 of the Criminal Code, namely the elements of "anyone", "intentionally", "premeditated", and "taking the life of another person" had been fulfilled legally and convincingly. The defendant, together with other perpetrators, was proven to have planned the murder within a certain period of time, which indicates that there was a time interval to think calmly, thus fulfilling the element of planning as referred to in Article 340 of the Criminal Code. In addition, the motive for the murder in this case was closely related to prolonged domestic conflict, jealousy, domestic violence, and deep disappointment with the victim. Psychological and social factors contributed to the defendant's decision to plan and carry out the murder together with others. The judge's decision to impose a life sentence reflects the application of the law that fully considers the elements of premeditated murder and the social impact it has caused. This study is expected to contribute to the enforcement of criminal law, particularly in gaining a deeper understanding of the element of planning in premeditated murder, as well as serving as an academic reference in the development of criminal law in Indonesia.